Modulation of death receptor-mediated apoptosis in differentiating human myeloid leukemia HL-60 cells - Vondrácek, J; Sheard, M A; Krejcí, P; Minksová, K; Hofmanová, J; Kozubík, A (Journal of leukocyte biology, 2001)
Differentiating myeloid cells may become resistant to various apoptotic stimuli. In the present study, dimethyl sulfoxide (DMSO) and all-trans retinoic acid (ATRA) were found to modulate the sensitivity of HL-60 cells to death receptor-mediated apoptosis in a time-dependent manner. During the early stages of differentiation, DMSO treatment increased the response of HL-60 cells to tumor necrosis factor alpha; (TNF-alpha), but enhanced responsiveness was lost during later differentiation stages. In contrast, ATRA treatment induced resistance to TNF-alpha-induced apoptosis. HL-60 cells were resistant to Fas-mediated apoptosis but were sensitized by culturing in serum-free conditions. Similar to its effect on TNF-alpha sensitivity, DMSO pretreatment augmented the response to Fas-mediated signaling, which coincided with increased expression of Fas on DMSO-pretreated cells. However, during the later stages of DMSO-induced differentiation, sensitivity to anti-Fas antibody-induced apoptosis declined significantly, although Fas expression was still elevated. The reduced sensitivity to anti-Fas treatment partially correlated with increased Fas-associated phosphatase-1 mRNA expression. Thus, regardless of either Fas up-regulation or potentiation of TNF-alpha-mediated apoptosis during early DMSO-induced differentiation, a slow increase in resistance to apoptosis mediated through these death receptors occurs during DMSO-induced differentiation, which contrasts with the rapid induction of resistance following treatment with ATRA.
Keywords: transportní proteiny; apoptóza; HL-60 buňky; Kinetics; Receptors, Tumor Necrosis Factor, Type II; Tretinoin; Dimethyl Sulfoxide; Tumor Necrosis Factor-alpha; CD antigeny; Apoptosis; Up-Regulation; tretinoin; Antibodies, Monoclonal; buněčná diferenciace; lidé; Leukemia, Myeloid; Proto-Oncogene Proteins c-bcl-2; protoonkogenní proteiny c-bcl-2; upregulace; messenger RNA; Protein Phosphatase 1; HL-60 Cells; antigeny CD95; Protein Tyrosine Phosphatase, Non-Receptor Type 13; kultivační média bez séra; RNA, Messenger; Humans; tyrosinfosfatasy; Antigens, CD; Carrier Proteins; Culture Media, Serum-Free; TNF-alfa; dimethylsulfoxid; Protein Tyrosine Phosphatases; Receptors, Tumor Necrosis Factor; fas Receptor; myeloidní leukemie; monoklonální protilátky; receptory TNF; Cell Differentiation; kinetika; proteinfosfatasa 1; tyrosinfosfatasa nereceptorového typu 13; receptory TNF - typ II